The influence of product quality on purchase interest with halal awareness as an intervening variable - Nofrida, Desi; Mesta, Hendri Andi (Universitas Negeri Padang, 2023)
The purpose of this study is to find out and analyze the extent to which the influence of product quality on purchasing interest with halal awareness as an intervening variable in